Presence of hepatitis E virus in testis of naturally infected wild boars. Issue 6 (1st September 2022) - Risalde, María A.; Frias, Mario; Caballero‐Gómez, Javier; Lopez‐Lopez, Pedro; Fast, Christine; Jiménez‐Ruiz, Saúl; Agulló‐Ros, Irene; Eiden, Martin; Jiménez‐Martín, Débora; García‐Bocanegra, Ignacio; Rivero, Antonio; Carlos Gómez Villamandos, José; et al.
Abstract: The hepatitis E virus (HEV) is the main cause of viral acute hepatitis in the world, affecting more than 20 million people annually. During the acute phase of infection, HEV can be detected in various body fluids, which has a significant impact in terms of transmission, diagnosis or extrahepatic manifestations. Several studies have isolated HEV in the genitourinary tract of humans and animals, which could have important clinical and epidemiological implications. So, our main objective was to evaluate the presence of HEV in testis of naturally infected wild boars ( Sus scrofa ). For it, blood, liver, hepatic lymph node and testicle samples were collected from 191 male wild boars. The presence of HEV was evaluated in serum by PCR, as well as in tissues by PCR and immunohistochemistry. Four animals (2.09%; 95%CI: 0.82–5.26) showed detectable HEV RNA in serum, being confirmed the presence of HEV‐3f genotype in three of them by phylogenetic analysis. HEV was also detected in liver and/or hepatic lymph nodes of the four animals by RT‐PCR, as well as by immunohistochemistry analysis. Only one of these wild boars also showed detectable viral load in testis, observing HEV‐specific labelling in a small number of fibroblasts and some Sertoli cells. Our results confirm the presence of HEV genotype 3 in naturally infected wild boar testis, although no associated tissue damage was evidenced. This study does not allow us to discard semen as a possible source of HEV transmission in suids. Future experimental studies are necessary to evaluate the impact of HEV genotype 3 on fertility and the possibility of transmission through sexual contact in this specie.